2012
DOI: 10.1002/jrs.4041
|View full text |Cite
|
Sign up to set email alerts
|

Raman and FTIR spectroscopy applied to the conservation report of paleontological collections: identification of Raman and FTIR signatures of several iron sulfate species such as ferrinatrite and sideronatrite

Abstract: Fossil materials that contain iron sulfide are well known for their instability when exposed to oxygen and humidity. This term however combines a great variety of materials showing different types of damages. Most of them consist of crystal efflorescence appearing on the surface and inside the matrix. In this work, a methodology was determined for the analysis of these damages by the use of Raman and infrared spectroscopy. The infrared and Raman signatures of a large set of iron sulfates were characterized. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 38 publications
1
27
0
1
Order By: Relevance
“…Identification and conservation report of these fossils can be found elsewhere (Rouchon et al, 2012). The three specimens are severely damaged by crystalline efflorescence that is related to iron(II) sulfates (rozenite, Fe II SO 4 , 4H 2 O and szomolnokite Fe II SO 4 , H 2 O) with some minor proportion of iron(III) sulfates (jarosite, KFe III 3 (SO 4 ) 2 (OH) 6 , in the case of sample 6891 and ferricopiapite, Fe III 2/3 Fe III 4 (SO 4 ) 6 (OH) 2 ·20H 2 O, in the case of sample 6889).…”
Section: Samples and Geological Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification and conservation report of these fossils can be found elsewhere (Rouchon et al, 2012). The three specimens are severely damaged by crystalline efflorescence that is related to iron(II) sulfates (rozenite, Fe II SO 4 , 4H 2 O and szomolnokite Fe II SO 4 , H 2 O) with some minor proportion of iron(III) sulfates (jarosite, KFe III 3 (SO 4 ) 2 (OH) 6 , in the case of sample 6891 and ferricopiapite, Fe III 2/3 Fe III 4 (SO 4 ) 6 (OH) 2 ·20H 2 O, in the case of sample 6889).…”
Section: Samples and Geological Settingsmentioning
confidence: 99%
“…Some of them, such as those of the Flouest collection, are today severely damaged by iron sulfate efflorescence (Rouchon et al, 2012). It often underlines the fossil (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Although not all fossils containing pyrite undergo oxidation, pyrite decay is one of the most serious problems faced in geological and palaeontological conservation, and the chemistry of pyrite and marcasite oxidation has been investigated in both mining and museum collections for decades [3,14]. Oxidation products of pyrite consist of sulphuric acid, various hydrated iron sulphates (Fe 2+ (SO 4 )·nH 2 O: szomolnokite, rozenite and so on) and also calcium sulphates (Ca(SO 4 )·2H 2 O gypsum), depending on the composition of the fossil and of the embedding matrix [2,3,13,15]. Usually they appear as yellowish or grey/white powder, commonly smell of sulphur and cover the surface of the specimen.…”
Section: Pyrite and Pyrite Decaymentioning
confidence: 99%
“…According to Howie [3] and Fellowes and Hagan [14], a maximum 30% RH is considered safe. On the other hand, Newman [15] and Larkin [2] suggested that 40%-45% RH is a more realistic threshold, because it could be more easily reached and kept stable. In addition, this value is more compatible with the requirements of other materials stored together with the pyritic specimens.…”
Section: Pyrite and Pyrite Decaymentioning
confidence: 99%
“…Traces of calcium carbonate should also be considered and, although its presence here is not exclusive for underdrawing layers, this mineral and related oxalic compounds have frequently been found in iron gall ink composition (Ferrer and Sistach, 2005). Recorded spectra also display characteristic absorption bands, due to the 3 antisymmetric stretching vibrations in sulfate functional groups in the range 1300-1000 cm −1 and typical bending assignment, which occurs around 680-600 cm −1 (Derrick et al, 2000;Rouchon et al, 2012). The bands at 1109 cm −1 and 672 cm −1 are typical for anhydrite (CaSO 4 ), and are related to the 3 antisymmetric stretch vibration and 4 antisymmetric bending vibration, respectively.…”
Section: Microanalysismentioning
confidence: 99%